Boost C++ application development cookbook - Polukhin, Antony (Packt Publishing, 2013)
Annotation Boost libraries are developed by professionals, tested on multiple platforms and processor architectures, and contain reliable solutions for a wide range of tasks. This Cookbook takes you on a journey of simplifying the process of application development and guides you through writing perfect applications fast."Boost C++ Application Development Cookbook" provides you with a number of clear step-by-step recipes that will help you take advantage of the real power of Boost and C++, while giving you a good grounding in using it in any project."Boost C++ Application Development Cookbook" looks at the Boost libraries, and breaks down the mystery and confusion about which library to use in which situation. It will take you through a number of clear, practical recipes that will help you to take advantage of the readily available solutions. Boost C++ Application Development Cookbook starts with teaching the basics of Boost libraries that are now mostly part of C++11 and leave no chance for memory leaks. Managing resources will become a piece of cake. Well see what kind of work can be done at compile time and what Boost containers can do. Do you think multithreading is a burden? Not with Boost. Think writing portable and fast servers is impossible? Youll be surprised! Compilers and operating systems differ too much? Not with Boost. From manipulating images to graphs, directories, timers, files, strings everyone will find an interesting topic. You will learn everything for the development of high quality fast and portable applications. Write a program once and then you can use it on Linux, Windows, MacOS, Android operating systems
Includes index.
Keywords: C++ (Computer program language); Computer programming.; elektronické knihy; electronic books